The view through the ventricle catheter – The new ShuntScope for the therapy of pediatric hydrocephalus - Senger, Sebastian; Antes, Sebastian; Salah, Mohamed; Tschan, Christoph; Linsler, Stefan; Oertel, Joachim (Journal of Clinical Neuroscience, 2018)
Purpose: Correct placement of the ventricle catheter directly influences the function of cerebral shunt systems. The incidence of proximal catheter misplacement reaches up to 45%. To avoid misplacements and revisions a new intra-catheter endoscope for precise ventricle catheter placement in children was evaluated. Methods: The semi-rigid ShuntScope (Karl Storz GmbH & Co.KG, Tuttlingen, Germany) with an outer diameter of 1.0 mm and an image resolution of 10,000 pixels was used in a series of 27 children and adolescents (18 males, 9 females, age range 2 months–18 years). Indications included catheter placement in aqueductal stenting (n = 4), first time shunt placement (n = 5), burr hole reservoir insertion (n = 4), catheter placement after endoscopic procedures (n = 7) and revision surgery of the ventricle catheter (n = 7). Results: ShuntScope guided precise catheter placement was achieved in 26 of 27 patients. In one case of aqueductal stenting, the procedure had to be abandoned. One single wound healing problem was noted as a complications. Intraventricular image quality was always sufficient to recognize the anatomical structures. In case of catheter removal, it was helpful to identify adherent vessels or membranes. Penetration of small adhesions or thin membranes was feasible. Postoperative imaging studies demonstrated catheter tip placements analogous to the intraoperative findings. Conclusions: Misplacements of shunt catheters are completely avoidable with the presented intra-catheter technique including slit ventricles or even aqueductal stenting. Potential complications can be avoided during revision surgery. The implementation of the ShuntScope is recommended in pediatric neurosurgery.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Hydrocephalus; Intra-catheter endoscope; Neuroendoscopy; Pediatrics; ShuntScope